2003
DOI: 10.1007/s10048-003-0148-x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of Duchenne muscular dystrophy skeletal muscle

Abstract: The primary cause of Duchenne muscular dystrophy (DMD) is a mutation in the dystrophin gene, leading to absence of the corresponding protein, disruption of the dystrophin-associated protein complex, and substantial changes in skeletal muscle pathology. Although the primary defect is known and the histological pathology well documented, the underlying molecular pathways remain in question. To clarify these pathways, we used expression microarrays to compare individual gene expression profiles for skeletal muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
103
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 19 publications
4
103
1
Order By: Relevance
“…The lack of dystrophin and the consequent disorganization of the membraneassociated cytoskeleton could induce a dysfunction of calcium influxes and releases, with cumulative consequences on fetal DMD myogenesis, and adult muscle damage. However, dystrophin absence might be more crucial, and might not simply unbalance the mechanical structure of plasma membrane but deeply modify gene expression, as suggested by previously published transcriptomic analysis of dystrophic muscles (Haslett et al, 2003;Ghahramani Seno et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…The lack of dystrophin and the consequent disorganization of the membraneassociated cytoskeleton could induce a dysfunction of calcium influxes and releases, with cumulative consequences on fetal DMD myogenesis, and adult muscle damage. However, dystrophin absence might be more crucial, and might not simply unbalance the mechanical structure of plasma membrane but deeply modify gene expression, as suggested by previously published transcriptomic analysis of dystrophic muscles (Haslett et al, 2003;Ghahramani Seno et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Other experiments have profiled gene expression against hierarchies of genes (Boer et al, 2002;Fluck et al, 2005;Haslett et al, 2003;Nikawa et al, 2004;Porter et al, 2004;Seale et al, 2004a;Wu et al, 2003). Since the viability of the stem cells in their stem-like capacity is observed to decline after tissue dissociation and flow cytometry, fatemapping experiments in other tissues have enabled investigators to follow the migration and multi-lineage differentiation of particular single cells [e.g.…”
Section: (3) Satellite Cells Also Play a Role As Clues To The Progresmentioning
confidence: 99%
“…Several microarray-based studies of gene expression in normal and diseased states have been performed on human skeletal muscles obtained at biopsy or autopsy (1,8,20,21,33) and on murine skeletal muscle obtained immediately postmortem (30,32,37,40). These studies identified a number of genes in various functional categories that are differentially expressed in the disease states, suggesting that major alterations in tissue have far-reaching consequences for gene expression.…”
mentioning
confidence: 99%